2003
DOI: 10.1038/sj.eye.6700257
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of the timolol/dorzolamide fixed combination vs latanoprost in exfoliation glaucoma

Abstract: Purpose To evaluate the safety and efficacy of the timolol/dorzolamide fixed combination vs latanoprost 0.005% in exfoliation glaucoma patients. Methods We randomized in an observermasked fashion 65 newly diagnosed exfoliation glaucoma patients to either the timolol/dorzolamide twice daily or latanoprost daily treatment for 2 months and then crossed these over to the other treatment. Results A total of fifty-four patients completed the study. After 2 months of chronic dosing, the morning intraocular pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 22 publications
0
24
0
5
Order By: Relevance
“…[6][7][8][9][10][11][12] All patients signed an Institutional Review Board approved informed consent form before enrollment. Previously treated patients underwent an untreated washout period comprising 4 weeks for brimonidine, or dorzolamide; 5 weeks for beta-blockers or the dorzolamide/timolol fixed combination; and 6 weeks for prostaglandin analogues.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] All patients signed an Institutional Review Board approved informed consent form before enrollment. Previously treated patients underwent an untreated washout period comprising 4 weeks for brimonidine, or dorzolamide; 5 weeks for beta-blockers or the dorzolamide/timolol fixed combination; and 6 weeks for prostaglandin analogues.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies clearly demonstrated that topical administration of latanoprost 0.005% once daily provided a steady reduction of the IOP during both the day and night in POAG and XFG. [7][8][9][10][11][12][13] To the best of our knowledge, no information is available regarding 24-h curve testing or the mean range of IOP with the newer medication such as travoprost or bimatoprost in patients with exfoliation syndrome (XFS) together with elevated IOP. The purpose of this study was to compare the effects of three PG analogues on the 24-h IOP curve in eyes with XFS and ocular hypertension (OH).…”
Section: Introductionmentioning
confidence: 99%
“…30,37 Unfortunately, to date there are limited data with respect to the efficacy of this medication in controlling the IOP in XFG. 38 In this current study, we investigated the diurnal IOP reduction at four time points covering a period of 12 daytime hours to help establish the potency of these two medications in XFG. Both treatments significantly reduced the diurnal baseline IOP.…”
Section: Discussionmentioning
confidence: 99%